Subtitle - Cheng, Xin; Chan, Lap Ki; Cai, Hongmei; He, Mei-yao; Li, Yunqing; yang, xuesong (Advances in Social Sciences Research Journal, 2021)
In order to investigate the correlation between teachers’ age and anatomy education online in China during the Covid-19 pandemic, we conducted a nationwide survey among the anatomists in three age cohorts (i.e., 30-39, 40-49, 50-59 years old) at the medical schools in mainland China, Hong Kong and Macau. Of the 359 respondents, there were 31% (n=108) anatomists aged 30-39, 46% (n=160) anatomists aged 40-49, and 23% (n=80) anatomists aged 50-59 years old, who were teaching clinical medicine students online at medical schools in China during the pandemic. The survey questionnaire contains the following items on online anatomy courses during the pandemic: theoretical sessions, practical sessions, active learning, assessment and perception. Based on the Chi-Square statistical analysis, although this study demonstrated that some noticeable differences existed in several items, we found the statistically significant difference was on “the formats of recording the theoretical sessions for asynchronous recorded broadcasting of online course”, among the three age groups, more teachers aged 30-39 chose to capture the PowerPoint presentation screen without the teacher appearing in the recorded video. Overall, this survey revealed that the teachers’ age and their teaching experience offline would not be the decisive factors in implementing anatomy online course effectively during the pandemic.